Comparison of the effect of wet and dry torrefaction on chemical structure and pyrolysis behavior of corncobs. (January 2015) - Zheng, Anqing; Zhao, Zengli; Chang, Sheng; Huang, Zhen; Zhao, Kun; Wei, Guoqiang; He, Fang; Li, Haibin
Highlights: Both wet and dry torrefaction removed hemicellulose from corncobs. Dry torrefaction caused more significant structural change than wet torrefaction. Wet torrefaction dramatically improved levoglucosan yield from fast pyrolysis. Abstract: Wet and dry torrefaction of corncobs was conducted in high-pressure reactor and tube-type reactor, respectively. Effect of wet and dry torrefaction on chemical structure and pyrolysis behavior of corncobs was compared. The results showed that hemicellulose could be effectively removed from corncobs by torrefaction. However, dry torrefaction caused severe degradation of cellulose and the cross-linking and charring of corncobs. X-ray diffraction analysis revealed that crystallinity degree of corncobs was evidently enhanced during wet torrefaction, but reduced during dry torrefaction as raising treatment temperature. In thermogravimetric analysis, wet torrefied corncobs produced less carbonaceous residues than raw corncobs, while dry torrefied corncobs gave much more residues owing to increased content of acid insoluble lignin. Pyrolysis–gas chromatography/mass spectroscopy analysis indicated that wet torrefaction significantly promoted levoglucosan yield owing to the removal of alkali metals. Therefore, wet torrefaction can be considered as a more effective pretreatment method for fast pyrolysis of biomass.